Transnationalism in Missionary Medicine - Gewurtz, Margo S. (Social sciences and missions, 2017)
Kala-azar is a parasitic disease that was endemic in India, parts of Africa and China. During the first half of the twentieth century, developing means of treatment and identification of the host and transmission vectors for this deadly disease would be the subject of transnational research and controversy. In the formative period for this research, two Canadian Medical missionaries, Drs. Jean Dow and Ernest Struthers, pioneered work on Kala-azar in the North Henan Mission. The great international prestige of the London School of Tropical Medicine and the Indian Medical Service would stand against recognition of the clinical discoveries of missionary doctors in remote North Henan. It was only after Struthers forged personal relations with Dr. Lionel. E. Napier and his colleagues at the Calcutta School of Tropical Medicine that there was a meeting of minds to promote the hypothesis that the sand fly was the transmission vector.